Financial Inclusion Beyond Payments : Policy Considerations for Digital Savings - World Bank Group (World Bank, Washington, DC, 2019)
The report discusses key policy issues that enable and constrain digital savings market development and offers policy considerations within the context of the G20’s High-Level Principles for Digital Financial Inclusion. Based on current market observations, three policy considerations seem most important for facilitating digital savings account deployments: Enable banking institutions to pursue digital savings partnerships with nonbank entities. Support the development of interoperability between banks and nonbank e-money issuers. Harmonize customer due diligence standards for emoney wallets and low-risk bank deposits.